Importance of Nanoparticles for the Delivery of Antiparkinsonian Drugs - Silva, Sara (Pharmaceutics, 2021)
Parkinson’s disease (PD) affects around ten million people worldwide and is considered the second most prevalent neurodegenerative disease after Alzheimer’s disease. In addition, there is a higher risk incidence in the elderly population. The main PD hallmarks include the loss of dopaminergic neurons and the development of Lewy bodies. Unfortunately, motor symptoms only start to appear when around 50–70% of dopaminergic neurons have already been lost. This particularly poses a huge challenge for early diagnosis and therapeutic effectiveness. Actually, pharmaceutical therapy is able to relief motor symptoms, but as the disease progresses motor complications and severe side-effects start to appear. In this review, we explore the research conducted so far in order to repurpose drugs for PD with the use of nanodelivery systems, alternative administration routes, and nanotheranostics. Overall, studies have demonstrated great potential for these nanosystems to target the brain, improve drug pharmacokinetic profile, and decrease side-effects.